Sistem za zajemanje, arhiviranje, spremljanje in analizo procesnih parametrov polkontinuiranega ulivanja v IMPOL-u, Slovenska Bistrica - Sabolič Mijovič, Mojca (Kovine zlitine tehnologije, 1997)
This paper describes system for data acquisition, monitoring, data archiving and casting process analysis developed for D.C. casthouse environment in IMPOL Slovenska Bistrica. The system is composed of the three personal computers that are used for casting planning, casting process monitoring and casting analysis.
Keywords: litje; parametri procesni; analize parametrov; litje polkontinuirano; livarstvo; procesi; analize; parametri; aluminijeve zlitine; aluminium alloy